Personal hygiene practices and socio-economic conditions as influential factors for intestinal parasitic infection in Dhaka city dwellers (Bangladesh Journal of Zoology, 2019)
A total of 200 stool samples were examined and five species of intestinal parasites were identified. Two of them were protozoans (Entamoeba histolytica and Giardia intestinalis) and the rest of which three species were nematode parasites (Ascaris lumbricoides, Trichuris trichiura and Strongyloids stercoralis). The overall prevalence of parasitic infection was 50%. Individually the prevalence of Ascaris lumbricoides, Entamoeba histolytica, Giardia intestinalis, Trichuris trichiura and Strongyloids stercoralis was 25%, 13%, 6%, 3.5% and 2.5%, respectively. Patients of different age and sex had a variable degree of infection. Children aged under ten years showed the highest prevalence (73.97%) compared to other groups. Accordingly, male patients were found slightly more susceptible to the infection (50.38%) compared to the female (49.29%). People belonging to different occupation and educational qualification had various degree of infection. As expected patients who had no education and poor monthly income, showed the highest prevalence of infection, 77.77% and 90%, respectively. Personal hygiene practices of the patients had much influence on the parasitic prevalence and rate of infection. Respectively 58.82%, 91.42%, 80% and 63.55% prevalence were found among the patients who used to drink unsafe water, wash hands without soap, stay barefooted most of the time and do not trim their nails regularly. The present study supposed to reveal that socioeconomic conditions and behavioral factors may influence the prevalence of parasitic infections.Bangladesh J. Zool. 47(1): 129-136, 2019